Sustainable Development in international relations theory: its presence or abscence. A proposal for a new paradigm - Morán-Blanco, Sagrario (Iberoamerican Journal of Development Studies, 2022)
Along with the goals and targets set up by the United Nations in the 2030 Agenda, the concept of Sustainable Development has a great significance in the discipline of International Relations, since the beginning of the new century. In fact, contents studied and analyzed by International Relations are very linked to practically all the issues addressed in the Sustainable Development Goals (hereinafter, SDGs). First, this paper aims at showing and analyzing the gradual incorporation of Sustainable Development into the theory of International Relations. Second, it raises a need for a mainstream that contributes, on the one hand, to the theoretical development of the discipline and, on the other, to the progress towards sustainability and that of the planet through the attainment of the SDGs. The mentioned mainstream could be called «Sustainable Development Paradigm».